Mapping neuro-disabilities and their dimensions among under 5 years of age children in the southern agricultural corridor of Tanzania: a preliminary baseline survey - Chilipweli, Peter M.; Basinda, Namanya; Sabuni, Paul Alikado; Hyera, Fredy; Liana, Upendojackline; Leeyio, Titus Robert; Nyanza, Elias C.; Ngowi, Awerasia Vera (Frontiers in Psychology, 2025)
BackgroundNeuro-disabilities involve impairments of the nervous system, affecting brain development and functioning. Due to limited scientific data on neuro-disabilities in Tanzania, this study examines maternal characteristics in high-risk areas, such as the Southern Agricultural Growth Corridor (SAGCOT).MethodsThis cross-sectional study sampled 286 children aged 0–5 years and their mothers in the SAGCOT region. Each mother selected the youngest child within the specified age range. Multi-stage sampling was used to choose clusters and areas for the study. The Malawi Developmental Assessment Tool (M-DAT) was used to assess the children’s developmental levels. Descriptive analysis determined distribution patterns, while multivariate analyses were performed to identify significant factors. Modified Poisson regression with robust standard errors estimated prevalence ratios (PRs) and their 95% confidence intervals (CIs).ResultsThe study included 286 mother–child pairs from four clusters: Ihemi, Kilombero, Ludewa, and Mbarali. The children’s median age was 24 months, with the majority aged between 13 and 48 months. Boys constituted a slight majority (59.4%). The majority of mothers were married (72.4%), had primary education (56.6%), and were engaged in non-farming occupations (56.3%). Neurodevelopmental assessments revealed that 11.2% of children were fully developed, while 88.8% exhibited development delays. Adjusted prevalence ratios (aPR) with 95% confidence intervals identified significant associations between developmental domains and demographic variables such as age, gender, marital status, and maternal occupation.ConclusionThe study highlights a high prevalence of neuro-disability among children in Tanzania’s southern corridor, revealing disparities across regions and the impact of factors such as gender and marital status. Targeted interventions are essential to address these developmental challenges effectively and promote optimal child development and wellbeing.